Energy Efficiency Tracking in Thai Manufacturing Sector by Decomposition Technique - Wongkot Wongsapai (2018)
© The Authors, published by EDP Sciences, 2016. This paper presents an analysis of energy saving and changes in energy intensities in Thai manufacturing sector by Logarithmic Mean Divisia Index decomposition technique. This method includes three effects consists of the energy intensity effect, the structural effect and the effect of the economic growth on the energy consumption in Thailand by using the 25-year annual data from 1990 to 2014, carried out in four phases; (i) before National Energy Conservation law, (ii) during the effect of the law, (iii) Transition period of the law from first to second version, and (iv) during the effect of the law (No.2). We found that the most effective intensity effect is in the third phase due to the effect of the implementation of new energy efficient equipment from the second phase by enforcement of the law, especially in non-metallic sector, while the first phase illustrates the lowest intensity effect due to the energy conservation law had not been occurred. However, due to the highest economic growth of the country and change from agricultural to industrial development direction, the first phase presents the most effective structural effect, then this effect continuously decreased by time. We also conclude that the energy conservation law have direct effect to energy efficiency of the country however, strictly individual regulation which have target to enforce to energy intensive industries is still required for sustainable energy efficiency improvement.